ANALISIS STRATEGI PENGEMBANGAN PEMASARAN DAN NILAI TAMBAH TIWUL INSTAN - Zulkarnain zulkarnain (Politeknik Negeri Lampung, 2017)
The agricultural sector occupies a strategic position compared with other sectors. It is evident from its role in employment and contribution to gross domestic product. Tiwul has high economic value because of its relatively high nutrient content. Therefore, the advantage of Tiwul as a substitute for rice can be socialized (Subahar, 2004). The purpose of this study was to analyze strategy of marketing and instant Tiwul added value development in Wonosari District, Pekalongan, of East Lampung regency. The method used in this research was SWOT analysis and added value analysis. Respondents were selected intentionally (purposive) in Wonosari Pekalongan District of East Lampung regency with a sample of 20 respondents composed of 10 producers and 10 traders in addition to direcly observe the added value of instant Tiwul by conducting interviews with KWT Tani home industry. The results of this study indicated that the strategies used to improve the marketing of instant Tiwul in Wonosari District of East Lampung regency Pekalongan showed coordinates of (0.34 ; -0.50) in which the coordinates entered quadrant II, that although facing a variety of threats, the company still has iternal strength. The strategy that should be applied is to take advantage of long-term opportunities by way of diversification strategy (product / market). Instant Tiwul marketing in Wonosari District of Pekalongan has the strength in term of Tiwul production quality and increasing amount of production, which can be used to counter the threat. Added value for producers of instant Tiwul per production in East Lampung district is Rp 9450.00.Â Keyword: Strategy, Development and Marketing, Instant Tiwul, Added Value